Karakteristik Fluiditas Hasil Pengecoran Al-7Si Metode Sand Casting Akibat Variasi Temperatur Tuang dan Tebal Saluran - Juniarta, I Kadek Agus; Sugita, I Ketut Gede; Dwidiani, Ni Made (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract Al-7Si alloy is a widely used alloy in automotive and engine components. Al-Si alloys have excellent castability especially at 5-13% silicon content. The sand casting method is carried out by pouring liquid metal into a prepared sand mold. Pouring temperature is very influential in the casting process. Fluidity is the ability to flow liquid metal in the mold cavity. This research uses the fluidity test piece method with variations in mold channel cavity thickness of 1.5; 2; 3; 4 and 5 mm. Pouring temperature variations of 750; 850 and 950°C. Fluidity increases in flow length with each increase in channel thickness and pouring temperature. The lowest fluidity occurs at a channel cavity thickness of 1.5 mm with a flow length of 10.6 mm at a casting temperature of 750°C and the highest fluidity occurs at a channel cavity thickness of 5 mm with a flow length of 470 mm at a casting temperature of 950°C. Keywords: Al-7Si, casting temperature, channel thickness, fluidity